Analisis Faktor-Faktor Kesiapan Pemerintah Daerah Dalam Menerapkan Permendagri Nomor 47 Tahun 2021 Perihal Pemanfaatan Aplikasi e-BMD Dalam Pengelolaan Barang Milik Daerah Kota Bukittinggi - Fadhil Muhamad; Anda Dwiharyadi; Yuhefizar Yuhefizar (Jurusan Akuntansi Politeknik Negeri Padang, 2022)
This study aims to analyze factors of the readiness of the Regional Government, especially the Bukittinggi City Government in implementing the Minister of Home Affairs Regulation Number 47 of 2021 and the E-BMD Application. The population in this study were all OPDs in Bukittinggi City, which amounted to 29 SKPD. The sampling method was carried out by using a purposive sampling technique to determine the sample. Sampling is done by taking samples from the population based on certain criteria. A total of 100 respondents participated in the study consisting of Regional Property Management Officers, OPD Property Administration Officers, OPD Property Managers and Assistant OPD Property Managers. The data collection technique is carried out using a questionnaire sent via Google Form. The results of the analysis using multiple regression show the Quality of Human Resources, Utilization of Technology and Information, Leadership Style and Organizational Culture that affect Readiness in the Implementation of Permendagri Number 47 of 2021 and E-Applications BMD. The results of the research have contributed to the government in preparing the implementation of regulatory changes.